Wybrane problemy gospodarki finansowej jednostek pomocniczych gminy - Kowalczyk, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The functioning of auxiliary units of communes causes a lot of not only social, but also legal doubts, particularly concerning their financial management. The study aims at showing these problems, as well as solving some of them. It concerns political issues associated with the unequal treatment of auxiliary units, the issue of financing these units from the state budget, as well as selected problems connected with the functioning of the auxiliary units fund. The financial management of communes is within the interest of more and more society members, which is why the issues raised in the paper seem topical.
Keywords: samorząd lokalny; budżet gminy; gmina; gminna jednostka pomocnicza; fundusz